Towards an Effective Local Development Plan: Coping with Planning Weaknesses in Good Economic Performing Municipalities - Astuti, Sri Juni Woro; Prasetyono, Dwi Wahyu; Yudhia, Onny Pramana (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
The Aim of this paper is to analyze weaknesses of planning mechanisms that lead to fallaciousness in the aspiration absorption process despite the good local economic growth performed by local governments. In addition at analyzing determinants of failure in synchronization of community aspirations and conducted by the legislative or executive level. The research is qualitative research in two municipalities. Namely the island city of Tarakan and the City of Lamongan, Indonesia. Both areas have been selected to obtain regional representation of Indonesia from Java and Kalimantan islands, and because these two areas are included in the category of good economic growth. Data collection used the mixed methods whereby interviews, observation, documentation, questionnaires and focus group discussions are performed. From the results of the analysis, it was found that firstly, there is a weakness in the local government capacity especially in conducting development planning process. Secondly, political interests still intervene in some of the policies in the process of establishing the local development plans. Thirdly, time differences in the absorption of aspirations between those made by board members and those carried out by government agencies results in differences or shifts in the aspirations proposed by the community. Based on this study, policy recommendations related to the importance of reformulation on the local development planning mechanism to be more integrated. Are local proposed development planning mechanism must be supported by a management information system that is more transparent, well documented, and more complete and accurate in supporting data and information.